X-ray grating-based phase tomography for 3D histology - Zanette, Irene; Weitkamp, Timm; Le Duc, Geraldine; Pfeiffer, Franz (RSC Advances, 2013)
We demonstrate how X-ray grating interferometry (XGI) can be used to obtain microscopic phase tomography data of soft tissue in which the information content is comparable to that of conventional histological sectioning and staining. In addition, XGI tomography is a genuine three-dimensional method which yields volume data with a density resolution down to 0.5 mg cm -3 and does not require freezing the sample or dehydrating and embedding it in a hard matrix such as paraffin. In this paper, we discuss the potential of XGI tomography for histopathology, and we compare results on the testicle of a rat with those obtained from histological sectioning and staining. © The Royal Society of Chemistry 2013.
CRIS-Team Scopus Importer:2023-03-08